Anti-cancer activity and brine shrimp lethality assay of the extracts and isolated compounds from Garcinia schomburgkiana Pierre - Chanchai Sukkum, Chakkree Lekklar, Krisana Chongsri, Sataporn Deeying, Chantragan Srisomsap, Nakin Surapanich, Pronrumpa Kanjanasingh, Sakchai Hongthong (Journal of Applied Pharmaceutical Science, 2025)
The present study aimed to assess the anti-cancer and brine shrimp lethality activities of the various extracts and the isolated compounds from Garcinia schomburgkiana Pierre. Guided by bioassay fractionation, the bioactive fruit extract was chromatographed leading to the isolation of three xanthones, norathyriol (1), macluraxanthone (2), and 10-O-methylmacluraxanthone (3). The isolated compounds were characterized and confirmed the chemical structure using spectroscopic information. Among these, 10-O-methylmacluraxanthone was discovered for the first time in this plant and its complete spectroscopic data was given. Compounds, macluraxanthone, and 10-O-methylmacluraxanthone, demonstrated potent cytotoxicity against all cancerous cell lines (THP-1, A549, and HepG2) and Vero cell line with ED50 ranging from 2.25 ± 0.14 to 5.26 ± 0.13 μM. Norathyriol exhibited moderate toxicity in brine shrimp lethality assay with LC50 153.39 μM.
Keywords: Garcinia schomburgkiana, norathyriol, macluraxanthone, xanthone, cytotoxicity